Consumo, digestibilidade de nutrientes e balanço de nitrogênio da silagem de capim-elefante com adição de pedúnculo de caju desidratado - Teles, Margareth Maria; Neiva, Neuman Miranda José; Clementino, Rossana Herculano; do Rêgo, Aníbal Coutinho [UNESP]; Cândido, Magno José Duarte; Restle, João (My University, 2010)
The nutritive value of elephant grass silages, with increasing levels of dehydrated cashew stalk (DCS) was evaluated. Five addition levels were studied (0; 4; 8; 12 and 16%), using 20 rams in a completely randomized design with five treatments (addition levels) and four replicates (animals). Intake and digestibility of dry matter (DM), organic matter (OM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), ether extract (EE), total carbohydrates (TC) and non-fibrous carbohydrates (NFC) were determined, as well as total digestible nutrients (TDN) and silages nitrogen balance (NB). DCS did not affect intakes of DM, OM, NDF, ADF, TC and TDN, neither digestibility of OM, CB, NDF, ADF and TC silages. Otherwise, the addition of DCS increased intakes of CP, EE and NFC and digestibility of EE, NFC, as well as TDN values and nitrogen balance. Inclusion of DCS showed linear decreasing digestibility of ADF. It is concluded that addition of DCS to silages of elephant grass up to 16% on a natural basis can be used as a forage source for ruminants.
Intake, nutrients digestibility and nitrogen balance of elephant grass silages added different levels of dehydrated cashew stalk
Keywords: Anacardium occidentale L.; Ensiling; Nutritive value; Sheep